2009
DOI: 10.1208/s12248-009-9081-8
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol)-Modified Proteins: Implications for Poly(lactide-co-glycolide)-Based Microsphere Delivery

Abstract: Abstract. The reduced injection frequency and more nearly constant serum concentrations afforded by sustained release devices have been exploited for the chronic delivery of several therapeutic peptides via poly(lactide-co-glycolide) (PLG) microspheres. The clinical success of these formulations has motivated the exploration of similar depot systems for chronic protein delivery; however, this application has not been fully realized in practice. Problems with the delivery of unmodified proteins in PLG depot sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 59 publications
2
28
0
Order By: Relevance
“…The amount of protein released reached a maximum of 6 ng/mL over a period of 28 d, an amount 100-to a 1000-fold higher than the endogenous CXCL1 production in ischemic and nonischemic hind limbs, respectively. Moreover, the maximum amount of released protein could potentially be increased by poly(ethylyne glycol) modification of CXCL1, as has been shown for other proteins (Diwan & Park, 2003;Pai et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
“…The amount of protein released reached a maximum of 6 ng/mL over a period of 28 d, an amount 100-to a 1000-fold higher than the endogenous CXCL1 production in ischemic and nonischemic hind limbs, respectively. Moreover, the maximum amount of released protein could potentially be increased by poly(ethylyne glycol) modification of CXCL1, as has been shown for other proteins (Diwan & Park, 2003;Pai et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
“…1,5,6 Many reports have shown that proteins can be unstable at the interface of organic solvents such as methylene chloride or ethylacetate, leading to protein unfolding and physical aggregation. Such destabiliza- tion processes eventually result in significantly reduced therapeutic effects of proteins in PLGA MSs.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, all such PLGA formulation products involve only peptides or synthetic chemical drugs, not protein drugs, because the optimal pharmaceutical application of proteins in PLGA depot systems has not been fully realized in practice. 1,5 Although the first protein-loaded PLGA MS (recombinant human growth hormone, Nutropin Depot™) had been approved in 1998, this was withdrawn from the market in 2004 due to several technical problems. In general, protein-loaded PLGA MSs have been plagued with typical problems in terms of rapid initial burst release, physicochemical instability, and bioactivity loss.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations